Moderating effects of gender on the relationship between financial knowledge, financial attitude and self-control and financial behaviour among college- bound Gen Y in Klang Valley, Malaysia - Maarof, Zuhairah (2015)
Bankruptcy cases among youth are increasing each year. A total of 20 percent from all bankruptcy cases in Malaysia consist of those aged 35 years old and below (Malaysian Department of Insolvency, 2012) – an age cohort specifically known as Generation Y. In comparison with the previous generation, this generation has unique personalities. Additionally, in future, they have the prospective of earning higher income upon completing college. Hence, this study is significant in an attempt to ensure that Generation Y are able to perform effective financial behaviour to help them avoid from possible financial crisis such as bankruptcy. The objectives of the study are to determine gender differences in financial behaviour, financial attitude, financial knowledge and self-control among Generation Y in college. Moreover, this study intends to determine the moderating effect of gender on the relationships between three variables (financial knowledge, financial attitude and self-control) and financial behaviour. The study utilises secondary data of a research project on “Generation Y’s Consumer Competency and Lifestyle” in 2012 which was funded through Research University Grant Scheme (RUGS). Data were collected among six public universities and three private universities in the Klang Valley area using self-administered questionnaires. Respondents were selected using stratified random sampling technique. A total of 2,068 respondents involved in the study. However, only 1,399 were usable and used in the study. From the collected data, descriptive, t-test and hierarchical regression analysis were conducted using IBM SPSS (Version 21) to meet the objectives of the study. Findings showed that gender differences exist in financial behaviour, financial knowledge and financial attitude of Generation Y. Female students were found to have higher financial knowledge and possessed more positive financial attitude compared to male students. However, behaviour wise, male students indicated that they practiced more effective financial behaviour than the female counterpart. Ironically, despite having higher financial knowledge and more positive financial attitude, female students were not at par with male students in the aspect of effective financial behaviour. Results of hierarchical regression analyses showed that the moderating effect of gender existed on the following: financial knowledge and financial behaviour; and financial attitude and financial behaviour. The relationships, specifically, between financial knowledge and financial behaviour; and financial attitude and financial behaviour were stronger among female than male. Therefore, being female would enhance the relationship between financial knowledge and financial behaviour; and financial attitude and financial behaviour. The moderating effect of gender on the relationship between self-control and financial behaviour were found to be insignificant. However, self-control was found to have direct influence on the financial behaviour. It means that self-control affect the way students behave financially regardless of the gender. In conclusion, gender has a significant influence on the relationship between financial knowledge and financial attitude, and financial behaviour. Therefore, parties directly or indirectly involve in financial socialization of youth such as financial educators, policy makers and parent should take into account gender differences in their dealing and intervention programmes.